Seaweed Farm Development Strategy (Eucheuma Cottonii) in the District of Kokas Fakfak Regency - Aulia Saraswaty; Andi Patimang (P3M Politeknik Negeri Bali, 2019)
The problems of seaweed farming in the Kokas District of Fakfak Regency in this study were formulated as follows: (1) how much the total cost, revenue, and income of seaweed farmers per production cycle; (2) what are the internal and external factors that influence the development of seaweed farming (3) what are the priority strategies that can be applied in the development of seaweed farming. The objectives of this study are: (1) to determine the total cost, revenue and income of seaweed farmers per production cycle; (2) determine internal and external factors that can influence the development of seaweed farming; and (3) determine priority strategies that can be applied in developing seaweed farming. The basic method used in this research is descriptive analytical method, the respondent taking is done by purposive sampling, external, internal, SWOT analysis, and QSP matrix analysis. The results achieved in this study are the average total cost incurred during one production is Rp. 13. 305,666.67. Admission is an average of Rp. 30,600,000, and the average income is Rp. 17,294,333.33. Internal and external factors, namely strength: the availability of sufficient labor, easy cultivation is carried out, good quality seaweed. Weaknesses: limited capital, quality of resources is still lacking, promotion is still lacking. Opportunities: market share is still wide, demand is increasing, the development of technological progress. Threats: weather, lack of government role, rising prices of production facilities. The priority strategy in the development of seaweed farming based on QSP matrix analysis is strategy II, which is maintaining the quality of seaweed to meet the increasing demand.